Ru(TAP)32+ uses multivalent binding to accelerate and constrain photo-adduct formation on DNA. Issue 60 (29th May 2019) - Vanderlinden, Willem; Kolbeck, Pauline J.; Frederickx, Wout; Konrad, Sebastian F.; Nicolaus, Thomas; Lampe, Carola; Urban, Alexander S.; Moucheron, Cécile; Lipfert, Jan
Abstract : At high local DNA concentrations, a photoactive Ru(ii ) complex forms photo-adducts more rapidly and with reduced promiscuity. Abstract : Ru(ii )-complexes with polyazaaromatic ligands can undergo direct electron transfer with guanine nucleobases on blue light excitation that results in DNA lesions with phototherapeutic potential. Here we use single molecule approaches to demonstrate DNA binding mode heterogeneity and evaluate how multivalent binding governs the photochemistry of[Ru(TAP)3 ] 2+ (TAP = 1, 4, 5, 8-tetraazaphenanthrene).